2017
DOI: 10.1161/hypertensionaha.116.08427
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Long-Term Blood Pressure Variability and 10-Year Progression in Arterial Stiffness

Abstract: Experimental studies conducted on animal and human endothelium suggested that higher systolic blood pressure (SBP) variability reduces bioavailability of nitric oxide and increases vascular smooth muscle cell proliferation. These vascular wall changes could stiffen the arterial wall. Using data from the Multi-Ethnic Study of Atherosclerosis, we investigated the association between long-term SBP variability and ten-year percent change in arterial stiffness among 1122 individuals (mean age 57 years, 46% Males at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 47 publications
0
68
1
3
Order By: Relevance
“…Increased long-term BPV was found to be associated with stroke [4], cardiovascular events [2], arterial stiffnes s [5] and decreased GFR [3] and is therefore considered an independent risk factor for all-cause and cardiovascular mortality in non-hemodialysis patients. These remain, however, less well-investigated in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased long-term BPV was found to be associated with stroke [4], cardiovascular events [2], arterial stiffnes s [5] and decreased GFR [3] and is therefore considered an independent risk factor for all-cause and cardiovascular mortality in non-hemodialysis patients. These remain, however, less well-investigated in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…The latter includes variations in BP that occur over more prolonged periods of time, such as days, weeks, months, seasons, and even years [1]. A growing number of studies performed in the general population have shown that BPV is a risk factor for target organ damage and mortality, independent of absolute BP level [2-5]. …”
Section: Introductionmentioning
confidence: 99%
“…These changes are influenced by hemodynamic forces 15,16 and extrinsic factors, such as hormones 17 and inflammatory mediators 18 , which may be related to sodium and glucose balance. 19 Arterial rigidity is modulated by means of a fine balance between production and degradation of elastin and collagen.…”
Section: Review Articlementioning
confidence: 99%
“…[4][5][6][7][8][9][10] Three interesting articles have been recently published in this journal regarding long-term visit-to-visit BPV (VVV). Tedla et al 11 showed that an increased VVV among 1122 untreated individuals was predictive of arterial stiffness progression after 10 years of follow-up. The 2 remaining papers reported data on the prognostic value of systolic VVV coming from 2 major trials: the observational extension of the ADVANCE trial (Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation) 12 and the SPRINT (Systolic Blood Pressure Intervention Trial).…”
mentioning
confidence: 99%